2020
DOI: 10.3390/ijms21062153
|View full text |Cite
|
Sign up to set email alerts
|

Gomisin N from Schisandra chinensis Ameliorates Lipid Accumulation and Induces a Brown Fat-Like Phenotype through AMP-Activated Protein Kinase in 3T3-L1 Adipocytes

Abstract: Obesity results from an imbalance between energy intake and energy expenditure, in which excess fat is stored as triglycerides (TGs) in white adipocytes. Recent studies have explored the anti-obesity effects of certain edible phytochemicals, which suppress TG accumulation and stimulate a brown adipocyte-like phenotype in white adipocytes. Gomisin N (GN) is an important bioactive component of Schisandra chinensis, a woody plant endemic to Asia. GN has antioxidant, anti-inflammatory and hepatoprotective effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…As found in multiple reports on the anti‐obesity effect of SCF extract (Park et al, 2012), our results also show SCF extract has inhibitory effects on lipid accumulation. Lignans are known as major functional components of SCF extracts in the context of obesity (Lee et al, 2020). Multiple studies show that though various lignans in SCF extracts have been reported to have an anti‐obesity effect, no previous report has mentioned the effects of SC on lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As found in multiple reports on the anti‐obesity effect of SCF extract (Park et al, 2012), our results also show SCF extract has inhibitory effects on lipid accumulation. Lignans are known as major functional components of SCF extracts in the context of obesity (Lee et al, 2020). Multiple studies show that though various lignans in SCF extracts have been reported to have an anti‐obesity effect, no previous report has mentioned the effects of SC on lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that dibenzocyclooctadiene lignans in SCF extracts have potent inhibitory effects on lipid accumulation (Lee et al, 2020; Nowak et al, 2019). However, despite evidence regarding the effect of SCF crude extract, few studies have examined the effects of Schisandra lignans, with the exceptions of gomisin N (Jang et al, 2017; Lee et al, 2020), schisandrin B (Kwan et al, 2017), and deoxyschizandrin (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Differentiated 3T3-L1 preadipocytes express brown adipocyte markers and increased mitochondrial respiration in response to catecholamines (117). While this has prompted testing of the browning effect of various compounds (103,125,130), it should be kept in mind that even upon β-adrenergic stimulation, the level of expression of the prototypical brown adipocyte marker UCP1 is low (7). 3T3-L1 cells may not be considered as a bona fide brown adipocyte model.…”
Section: Cell Linesmentioning
confidence: 99%
“…Lee et al [29] discovered that schisandrol A, schizandrin A, gomisin N and schisandrin C in S. chinensis can inhibit α-glucosidase, with schisandrin C being the most potent inhibitor. It has been reported that gomisin N can inhibit adipogenesis during adipocyte differentiation, increase the expression of thermogenic factors such as uncoupling protein 1 and also enhance fatty acid oxidation in 3T3-L1 cells (mouse embryonic fibroblasts) [30]. Kwan group [31] reported that schisandrin B can significantly reduce the size of subcutaneous adipocytes, subcutaneous adipose tissue mass, and body weight in mice.…”
Section: Identification Of Active Compounds In S Chinensismentioning
confidence: 99%